Self-concept as an artifact evaluation method : generating evidence of the use of self-concept as an artifact evaluation method trhough the application in feature films - NEVES, Cecília Eloy (2021)
Through evaluating diverse films, this research aims to generate further evidence on the use of the Self-concept as a method capable of evaluating various artifacts. The Self-concept is conceptualized by Rosenberg (1979) as "the totality of thoughts and feelings that a person has about him/herself," and this variable has been used in recent studies as a method capable of characterizing the user, evaluating artifacts, and predicting the market success of various artifacts. Despite being a variable initially studied in psychology, since the 60s, it has been applied in the marketing area to understand the users' purchasing behavior. Studies have claimed that the greater the identification of the user with the image of the artifact or the idea of the possible use of the artifact, the greater the chances of purchasing. Moreover, one way to measure this is through the Self-concept questionnaire. It has already been used to characterize the user and evaluate artifacts in the design area. However, few studies still evidence the use of this method to assess artifacts, and even fewer show its ability to encapsulate the user experience and predict market success. There is a need for methods to understand the user and the experience in design and the film. Studies aiming to propose systems and mathematical equations capable of characterizing the user to recommend films are pretty standard, but few consider the whole experience of watching a film. This research aims to generate evidence on using the Self-concept as a method used in the design, user experience, and film evaluation.